2019
DOI: 10.1155/2019/7896749
|View full text |Cite
|
Sign up to set email alerts
|

Ipilimumab- and Nivolumab-Induced Colitis Causing Severe Hypokalemia and QTc Prolongation

Abstract: Immune-mediated colitis is an uncommon but well-documented adverse event in patients receiving nivolumab or ipilimumab therapy. In this report, we present a 69-year-old man who developed severe hypokalemia and colitis with significant corrected Q-T segment (QTc) prolongation as a result of combination nivolumab-ipilimumab immunotherapy for clear cell renal cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…[ 90 ] found that hypokalemia (19%) and hypercalcemia (10%) were the most common reported electrolyte abnormalities after hyponatremia. Hypokalemia can result from gastrointestinal losses secondary to immune-mediated colitis [ 91 , 92 ] or kidney losses due to renal tubular dysfunction [ 93 , 94 ]. Both distal and proximal renal tubular acidosis (RTA) have been described in various case reports, and most cases had concomitant AKI [ 94–97 ].…”
Section: Electrolyte and Metabolic Disturbances Associated With Icimentioning
confidence: 99%
“…[ 90 ] found that hypokalemia (19%) and hypercalcemia (10%) were the most common reported electrolyte abnormalities after hyponatremia. Hypokalemia can result from gastrointestinal losses secondary to immune-mediated colitis [ 91 , 92 ] or kidney losses due to renal tubular dysfunction [ 93 , 94 ]. Both distal and proximal renal tubular acidosis (RTA) have been described in various case reports, and most cases had concomitant AKI [ 94–97 ].…”
Section: Electrolyte and Metabolic Disturbances Associated With Icimentioning
confidence: 99%
“…Several reported cases illustrate the potential for severe hypokalemia related to immunotherapy resulting from gastrointestinal or kidney losses. Immune-mediated gastritis and colitis have been described with associated hypokalemia (41,42). Hypokalemia from kidney losses can also be induced by ICIs (43)(44)(45)(46).…”
Section: Hypokalemiamentioning
confidence: 99%